2021
DOI: 10.1016/j.heliyon.2021.e07906
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic weight-bearing test during jumping: A sensitive outcome measure of chronic osteoarthritis pain in rats

Abstract: Pain due to osteoarthritis (OA) often occurs during locomotion in the vertical direction when joints are subjected to high mechanical load, e.g. during standing up from a chair or using stairs. To investigate joint pain in OA rat models, dynamic weight-bearing or gait analysis is traditionally conducted during horizontal walking on a flat surface. However, in chronic models of OA, which are of particular translational relevance for the disease, differences in the readouts between OA and control rats are often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In 2021, a rodent colony study with Zilretta showed its possible effect in reducing the difficulty of weightbearing load on the joint. 72 While literature has described a lesser risk for adverse events with Zilretta compared with traditional glucocorticoids, the website for Zilretta (www.zilretta.com) lists potential side effects as "joint pain, headache, joint swelling, back pain, sore throat and runny nose, upper…”
Section: Kgn and Nanoparticlesmentioning
confidence: 99%
See 3 more Smart Citations
“…In 2021, a rodent colony study with Zilretta showed its possible effect in reducing the difficulty of weightbearing load on the joint. 72 While literature has described a lesser risk for adverse events with Zilretta compared with traditional glucocorticoids, the website for Zilretta (www.zilretta.com) lists potential side effects as "joint pain, headache, joint swelling, back pain, sore throat and runny nose, upper…”
Section: Kgn and Nanoparticlesmentioning
confidence: 99%
“… 40 , 55 , 81 KGN is known to be chondrogenic, as confirmed in multiple ex vivo cultures and animal models of hyaline cartilage where KGN was shown to stimulate proliferation of cartilage stem cell progenitors. 55 , 72 , 79 , 81 In vitro studies of human chondrocyte OA models have demonstrated that KGN administration results in increased collagen 2:1 expression and decreased matrix metalloproteinase (MMP) expression, promoting the innate properties that support the function of articular cartilage. 40 , 72 These studies have also shown increases in gene expression of interleukin-6 (IL-6) and its receptor, revealing an anti-inflammatory mechanism.…”
Section: Hydrogel Injectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-1β changes chondrocyte homeostatic stability by elevating reactive oxygen species formation, inhibiting anabolic function, and inducing articular cartilage breakdown [12]. Generally, OA patients suffer from periodic arthralgia (joint pain), stiffness, and locomotor restriction symptoms [13, 14]. Among these, the substantial problem for the majority of patients is related to pain [15].…”
Section: Introductionmentioning
confidence: 99%